Shared Control Schemes for Middle Ear Surgery - So, Jae-Hun; Sobucki, Stéphane; Szewczyk, Jérôme; Marturi, Naresh; Tamadazte, Brahim (Frontiers in Robotics and AI, 2022)
This paper deals with the control of a redundant cobot arm to accomplish peg-in-hole insertion tasks in the context of middle ear surgery. It mainly focuses on the development of two shared control laws that combine local measurements provided by position or force sensors with the globally observed visual information. We first investigate the two classical and well-established control modes, i.e., a position-based end-frame tele-operation controller and a comanipulation controller. Based on these two control architectures, we then propose a combination of visual feedback and position/force-based inputs in the same control scheme. In contrast to the conventional control designs where all degrees of freedom (DoF) are equally controlled, the proposed shared controllers allow teleoperation of linear/translational DoFs while the rotational ones are simultaneously handled by a vision-based controller. Such controllers reduce the task complexity, e.g., a complex peg-in-hole task is simplified for the operator to basic translations in the space where tool orientations are automatically controlled. Various experiments are conducted, using a 7-DoF robot arm equipped with a force/torque sensor and a camera, validating the proposed controllers in the context of simulating a minimally invasive surgical procedure. The obtained results in terms of accuracy, ergonomics and rapidity are discussed in this paper.